Promoting social plasticity in developmental disorders with non-invasive brain stimulation techniques - Boggio, Paulo S.; Asthana, Manish; Costa, Thiago Leiros; Valasek, Claudia A.; Osório, Ana A. (Frontiers in Neuroscience, 2015)
Being socially connected directly impacts our basic needs and survival. People with deficits in social cognition might exhibit abnormal behaviors and face many challenges in our highly social-dependent world. These challenges and limitations are associated with a substantial economical and subjective impact. As many conditions where social cognition is affected are highly prevalent, more treatments have to be developed. Based on recent research, we review studies where non-invasive neuromodulatory techniques have been used to promote Social Plasticity in developmental disorders. We focused on three populations where non-invasive brain stimulation seems to be a promising approach in inducing social plasticity: Schizophrenia, Autism Spectrum Disorder (ASD) and Williams Syndrome (WS). There are still very few studies directly evaluating the effects of transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS) in the social cognition of these populations. However, when considering the promising preliminary evidences presented in this review and the limited amount of clinical interventions available for treating social cognition deficits in these populations today, it is clear that the social neuroscientist arsenal may profit from non-invasive brain stimulation techniques for rehabilitation and promotion of social plasticity.